2016
DOI: 10.1016/j.addbeh.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Negative urgency mediates the relationship between childhood maltreatment and problems with alcohol and cannabis in late adolescence

Abstract: These findings provide support for negative urgency as a unique mediator of the associations between childhood maltreatment and both alcohol and cannabis problems, suggesting that future work on mechanisms in these associations should focus on mood-based impulsivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
53
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 48 publications
8
53
0
4
Order By: Relevance
“…Recently, colleagues (2015, 2016) were able to replicate the protective effect of alcohol PBS use on alcohol outcomes, as well as most of the direct effects of antecedent variables on alcohol PBS use, including age at drinking onset (positive), drinking motives (negative), and impulsivity-like traits 2 (negative; Bravo et al, 2015Bravo et al, , 2016. Similar to what has been found in the alcohol field, male sex (Johnston et al, 2015), earlier age at first use (Chen et al, 2009), impulsivity-like traits (Kaiser et al, 2012;Robinson et al, 2014;Wardell et al, 2016), and marijuana use motives (Simons et al, 1998;Zvolensky et al, 2007) have all been shown to be risk factors associated with increased marijuana use, consequences, and/or dependence. However, given the nascence of the marijuana PBS field, no studies have examined whether marijuana PBS use mediates the associations between these antecedents and marijuana-related outcomes.…”
supporting
confidence: 63%
“…Recently, colleagues (2015, 2016) were able to replicate the protective effect of alcohol PBS use on alcohol outcomes, as well as most of the direct effects of antecedent variables on alcohol PBS use, including age at drinking onset (positive), drinking motives (negative), and impulsivity-like traits 2 (negative; Bravo et al, 2015Bravo et al, , 2016. Similar to what has been found in the alcohol field, male sex (Johnston et al, 2015), earlier age at first use (Chen et al, 2009), impulsivity-like traits (Kaiser et al, 2012;Robinson et al, 2014;Wardell et al, 2016), and marijuana use motives (Simons et al, 1998;Zvolensky et al, 2007) have all been shown to be risk factors associated with increased marijuana use, consequences, and/or dependence. However, given the nascence of the marijuana PBS field, no studies have examined whether marijuana PBS use mediates the associations between these antecedents and marijuana-related outcomes.…”
supporting
confidence: 63%
“…Sensation seeking was associated with tobacco and drug use frequency in both adolescence (Crawford et al, 2003; Spillane et al, 2012; Stautz & Cooper, 2014) and adulthood (Cyders et al, 2009; Krank et al 2011; Perkins et al, 2008), although some research has failed to find a significant relationship (Adams et al, 2012; Wardell et al, 2016; Albein-Urios et al, 2012; Dvorak & Day, 2014). Lack of premeditation was linked to tobacco use, problematic drug use, and SUDs especially in adulthood (Adams et al, 2012; Lee et al, 2015; Moreno-López et al, 2012; Torres et al, 2013; Wardell et al, 2016).…”
Section: Review Of Impulsive Behavior and Drug Use In Adolescence mentioning
confidence: 99%
“…Lack of premeditation was linked to tobacco use, problematic drug use, and SUDs especially in adulthood (Adams et al, 2012; Lee et al, 2015; Moreno-López et al, 2012; Torres et al, 2013; Wardell et al, 2016). The research on lack of perseverance has produced mixed results with most studies failing to demonstrate a strong relationship (Albein-Urios et al, 2012; Settles et al, 2012).…”
Section: Review Of Impulsive Behavior and Drug Use In Adolescence mentioning
confidence: 99%
See 2 more Smart Citations